'The Great Britain of the South': the Law of Contract in Early Colonial New Zealand. Issue 1 (21st October 2019) - Swain, Warren
Abstract: Some nineteenth century writers like the Scottish born poet William Golder, used the term 'the Great Britain of the south' as a description of his new home. He was not alone in this characterisation. There were of course other possible perspectives, not least from the Māori point of view, which these British writers inevitably fail to capture. A third reality was more specific to lawyers or at least to those caught up in the legal system. The phrase 'the Great Britain of the south' fails to capture the complexity of the way that English law was applied in the early colony. The law administered throughout the British Empire reflected the common law origins of colonial legal systems but did not mean that the law was identical to that in England. Scholars have emphasised the adaptability of English law in various colonial settings. New Zealand contract law of this time did draw on some English precedents. The early lawyers were steeped in the English legal tradition. At the same time, English authorities were used with a light touch. The legal and social framework within which contract law operated was also quite different. This meant, for example, that mercantile juries were important in adapting the law to local conditions. Early New Zealand contract law provides a good example of both the importance of English law in a colonial setting and its adaptability.